(untitled) (Jurnal Teknologi (Sciences & Engineering), 2013)
PSf flat sheet membrane was prepared via phase inversion technique with N-methyl-2-pyrroidone (NMP) as solvent. In this study polyethylene glycol (PEG) and polyvinylpyrollidone (PVP) were compared as additives at different composition (0.5 wt%, 1 wt%, 3 wt% and 5 wt%). The structure and morphology of the resulting membranes were observed by scanning electron microscope (SEM) and the membranes permeation were evaluated in terms of pure water flux (PWF) and solute rejection. Solution of bovine serum albumin (BSA) was used to study the performance of prepared membrane. The addition of the additives into the casting solution changed the structure of the resultant membranes, which was believed to be associated with the change the permeated of water. The results demonstrated that at the same additive content, PSf/PVP membranes had higher PWF at 0.5 wt% and and 5 wt% of additive while PSf/PEG at 1 wt% and 3 wt% of additive. The BSA rejection show no significant changes for PSf/PEG while PSf/PVP, BSA rejection decrease with increase the increasing the PVP. For PEG, additive from 0% to 5%, the PWF increased from 14.73 at to 101.85 LMH. While for PVP, the PWF increased from 21.13 to 177.61 LMH. The membrane morphology showed that all images showed the membranes were having asymmetric structure consisting of a dense top layer, a porous sublayer, and a small portion of sponge-like bottom layer. The top layer of the membrane consist of finger-like structure while at bottom layerÂ has macrovoid structure. With increasing the additive, the finger-like structure become longer to the bottomÂ and macrovoid become smaller. The study found that PEG gives the optimum performance based on the result of rejection and flux permeation.